Direct-to-consumer advertising effects on nurse–patient relationship, authority, and prescribing appropriateness - Filipova, Anna A (Nursing ethics, 2018)
Background:Discussing direct-to-consumer advertising of prescription drugs during a visit could affect prescribing practices and provider–patient relationship.Research objectives:The study examines advanced practice nurse prescribers’ perceptions of direct-to-consumer advertising and its effects on nurse–patient relationship, prescriptive authority, and appropriateness of patient clinical requests.Research design:A cross-sectional survey design was implemented.Participants and research context:The random sample consisted of 316 nurses (27.17% response rate) in one of the Midwestern states in the United States. Pearson’s chi-square analysis and multiple/multinomial logistic regression analyses were used.Ethical considerations:Permission to conduct the study was obtained from the university’s Institutional Review Board. Participation was voluntary, and measures were taken to protect the anonymity and confidentiality of consenting participants.Findings:Most nurses (69%) believed that patients were “poor or very poor” at assessing the relevance of drug advertisements, 61% reported that the increase in drugs advertisements directed at patient was “a bad or a very bad thing,” and only 16% thought the advertisements were accurate to “a very or to a great extent.” Improved nurse–patient relationship was associated with factors such as the patient not bringing printed material, seeking nurse’s opinion only, taking responsibility for their health, and not challenging nurse’s prescriptive authority.Discussion:Advertising discussion during a visit could improve as well as pose a challenge to a nurse–patient relationship and nurse’s prescriptive authority.Conclusion:The positives of discussing advertising information can be maximized and the negatives minimized through enhanced interpersonal nurse–patient communication.